ESTIMASI KARBON STOK PADA PEPOHONAN DI ARBORETUM LABORATORIUM SUMBERDAYA HAYATI KALIMANTAN (LSHK), UNIVERSITAS MULAWARMAN SAMARINDA - Rita Diana; Oscar Situmorang; Hastaniah Hastaniah; Sutedjo Sutedjo; Chandradewana Boer (Tengkawang : Jurnal Ilmu Kehutanan, 2022)
The arboretum is a collection of various plants or vegetation that has been planted for research and education purposes. Furthermore, vegetation is a carbon dioxide gas absorbent and an oxygen-producing source, both of which are required by living things as a source of breathing. The objective of this study is to estimate carbon accumulation and potential carbon dioxide absorption with vegetation in the arboretum of the LSHK, as well as to understand the contribution of each type of vegetation in the arboretum to carbon dioxide absorption. The method used in this study is a census form which then measures both diameter and height on all vegetation larger than 5 cm in diameter. Allometries are used to analyze carbon accumulation and carbon dioxide absorption. Field measurements revealed 44 trees and 17 sapling species, 24 families, and 352 individuals. Aquilaria malaccensis has the most extensive carbon stock of trees, with 17,610.41 kg/species; Anisoptera costata comes in second, with 11,497.75 kg/species.Arenga pinnata, on the other hand, has the lowest carbon stock, with an average of 8.32 kg/individual tree. The species Aquilaria malaccensis has the most extensive carbon stock of saplings, with 35 individuals and 239.52 kg/species of total carbon stock. Meanwhile, Diospyros blancoi is the first lowest carbon stock, with a total of 0.54 kg/species. Aquilaria malaccensis has the highest potential for carbon dioxide absorption of any tree, with 64,571.52 kg/species. Otherwise, Arenga pinnata has the lowest value of 30.49 kg/species. The most significant result for saplings was Aquilaria malaccensis, with a value of 878.24 kg/type, followed by Diospyros blancoi, with a value of 1.99 kg/species.Keywords: Tree, Sapling, Carbon stock, ArboretumAbstrakArboretum adalah koleksi berbagai jenis tanaman atau vegetasi yang ditanam untuk penelitian, pendidikan. Selain itu, vegetasi juga merupakan penyerap gas karbon dioksida dan penghasil oksigen yang dibutuhkan oleh makhluk hidup sebagai sumber pernapasan. Tujuan penelitian ini adalah untuk memperkirakan akumulasi karbon dan potensi penyerapan karbon dioksida dengan vegetasi di Arboretum Laboratorium Sumber Daya Hayati Kalimantan, mengetahui kontribusi setiap jenis vegetasi dalam Arboretum dalam penyerapan karbon dioksida. Metode yang dilakukan dalam penelitian ini adalah dalam bentuk sensus pada semua vegetasi yang berdiameter ≥ 5 cm, mengukur diameter dan tinggi. Analisis akumulasi karbon dan penyerapan karbon dioksida dilakukan menggunakan allometrik. Pengukuran lapangan menemukan 44 spesies pohon dan 17 jenis sapihan, 24 famili, dan 352 individu. Analisis data yang diperoleh stok karbon pohon yang paling besar adalah Aquilaria malaccensis dengan 17.610,41 kg/jenis, selanjutnya yang kedua adalah Anisoptera costata, dengan 11.497,75 kg/jenis. Di sisi lain, stok karbon terendah adalah Arenga pinnata dengan nilai 8,32 kg/jenis. Stok karbon sapihan yang paling besar adalah spesies Aquilaria malaccensis, dengan 35 individu dan 239,52 kg/jenis dari total stok karbon. Sementara itu, Diospyros blancoi, dengan jumlah 0,54 kg/jenis, merupakan stok karbon terendah pertama. Potensi penyerapan karbon dioksida untuk pohon yang diperoleh hasil yang paling besar adalah Aquilaria malaccensis dengan nilai 64.571,52 kg/jenis, yang terendah adalah Arenga pinnata dengan nilai 30,49 kg/jenis, dan untuk sapihan didapat hasil yang terbesar Aquilaria malaccensis dengan nilai 878,24 kg/jenis lalu yang terendah Diospyros blancoi dengan nilai 1,99 kg/jenis.Kata kunci: Pohon, Sapihan, Stok karbon, Arboretum